Ý định lựa chọn địa điểm ăn uống của người dùng thế hệ Z: Vai trò của truyền miệng điện tử và sự tương đồng - Nguyễn Thị Mỹ, Nguyệt; Lê Bảo, Ngọc; Nguyễn Thị Thủy, Chung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
Based on an integrated model of the theory of planned behavior and self-congruity theory, this paper aims to examine Generation Z’s intention to choose food and beverage destinations. Data was collected from 225 consumers aged between 14 and 25 years old. Partial least squares structural equation modeling (PLS-SEM) was applied to test hypothesized relationships. The results showed a positive and significant effect of electronic word-of-mouth on consumers’ attitudes, subjective norms, perceived behavioral control, and food and beverage destination choice intention. Furthermore, a positive moderating effect of self-congruity exists on the relationship between electronic word-of-mouth and attitudes, as well as those between electronic word-of-mouth and perceived behavioral control. This study provides fresh insights into how food and beverage businesses can leverage social media to attract more Generation Z consumers.